ANALISIS PERGESERAN KEGIATAN EKONOMI JAWA TIMUR MELALUI PENGUATAN KEARIFAN LOKAL - Setyo Wahyu Sulistyono (Program Studi Ekonomi Pembangunan, 2021)
The purpose of this study is to analyze economic performance by sector through analysis of the basic and non-basic sectors, as well as to see the shifts in economic activities that have occurred in the East Java region. The research method is carried out with a descriptive quantitative approach using secondary data types, obtained on the information of a second party as a competent data provider. The analysis technique used is location quetiont (lq) analysis and descriptive qualitative approach as a method in determining the basis and non-base sectors as well as shifting economic activities by taking the location of East Java. The change in the structure of the economy can also be seen from the change in the contribution of each sector to GDP / GRDP. The results of the study are that there is a shift in economic activity with a jump in the economic phase from the primary economy to services with the acceleration of industrialism, the industrial and service sectors have become the movers in the last 3 years, industry. processing has become a new trend in economic acceleration, the service and warehousing sectors have become pockets in the economy characterized by strengthening local wisdom by strengthening competitiveness so as to be able to provide economic resources for the domestic and be able to provide for foreign domestic needs for excess production with a basic sector concept based on real local wisdom